Protective Effects of Aqueous Extract of Baillonella toxisperma Stem Bark on Dexamethasone-Induced Insulin Resistance in Rats - Marius Trésor Wego; Sylviane Laure Poualeu Kamani; David Miaffo; Moise Legentil Nchouwet; Albert Kamanyi; Sylvie Léa Wansi Ngnokam (Hindawi Limited, 2019)
The aim of this study was to evaluate the effects of the aqueous extract of Baillonella toxisperma stem bark on dexamethasone-induced insulin resistance in rats. A quantitative phytochemical study was done on the aqueous extract of Baillonella toxisperma for the total phenol, flavonoid, and flavonol determination. Insulin resistance was induced by intraperitoneal injection of dexamethasone (1 mg/kg) for 8 days, one hour before oral administration of different treatments (extract at doses of 60, 120, and 240 mg/kg and metformin at 40 mg/kg). During the test, body weight and blood glucose level were evaluated on days 1 and 8. At the last day of treatment, the glucose tolerance test was performed in rats; after that, blood samples were collected for triglycerides, total cholesterol, LDL and HDL cholesterols, transaminases (ALT and AST), and total protein level determination. Organs (heart, liver, pancreas, and kidneys) were also collected for the relative organ weight determination. The results showed that the aqueous extract of B. toxisperma is rich in total phenols, flavonoids, and flavonols. This extract significantly reversed the metabolic alterations (lipid profile, protein level, and transaminase activity) induced by dexamethasone in rats. At doses of 120 and 60 mg/kg, Baillonella toxisperma also significantly decreases (p<0.05; p<0.01) postprandial hyperglycemia in insulin resistance rats. The results suggest that Baillonella toxisperma can manage insulin resistance and may be useful for the treatment of type 2 diabetes mellitus.